Comparison of the diversity of ground beetle (Coleoptera: Carabidae) assemblages in small and large temperate peat bogs - Gennadi G. Sushko; Sergey V. Buga; Yulia I. Novikova (Mires and Peat, 2024)
We present a study comparing assemblages of ground beetles between small and large pristine peat bogs in Central-Eastern Europe, to better understand biodiversity variability in peatland ecosystems in tundra patches in the temperate zone. We found that Shannon diversity and Pielou evenness indices and species composition for carabid assemblages of small peat bogs were significantly higher compared to large peat bogs. However, NMDS ordination revealed a high similarity between the assemblages of open habitats in peat bogs of different sizes. Regardless of peat bog size, assemblages included mostly specialised, medium-sized and flightless species. The predominance of habitat specialists with poor dispersal ability indicates that the habitat conditions in both small and large peat bogs are stable in the region. Small peat bogs were represented by a higher number of open habitat and forest dweller species, but their abundances were not high. When comparing ground beetle assemblages of small peatlands and adjacent pine forests on mineral soils, clear differences in diversity, species composition, imago body size and flight ability were revealed. Only some forest dwellers were recorded in peat bog habitats, while peat bog specialists were not found in the pine forests. Consequently, even small peat bogs can support highly specialised species assemblages and represent an environmental filter (probably due to the high humidity and acidity of Sphagnum mosses), which can exclude most generalist species and species from adjacent habitats.